Radio Programme on how to Control Stemborers in Maize and Sorghum - Mubiru, Wasswa (Technical Centre for Agricultural and Rural Cooperation, 2008)
Stemborers are dangerous insect pests in Uganda. They are capable of destroying a great deal of the maize and sorghum plants. Crops between 3 to 5 weeks old are at a higher risk of attack by the Stemborer caterpillar. Stemborers are notorious for killing or stunting corn rows next to fences, grassed waterways, and conservation terraces. How do stemborers get into your maize or sorghum crop? It happens when moths lay eggs on the plant. The eggs hatch in about two to five days. The freshly hatched caterpillars migrate towards the central shoot where they first feed on the tender leaves for sometime. Later on they bore into top internode and move downwards. In case of younger plants, the growing point gets badly damaged resulting into the drying up of the central shoot.